(untitled) (Research, Society and Development, 2021)
The aim of this study was mapping and describe the actions developed for the bees conservation in educational meliponaries in the Northeast region of Brazil. For this purpose, a form was sent via Whatsapp or Direct on Instagram, with questions addressed to the stingless beekeepers and/or representatives of identified institutions. To perform the mapping, the Google My Maps Platform was used. Thus, 20 educational meliponaries were identified in their majority (75%), built and maintained through efforts and individual initiatives of their coordinators and, even the projects maintained by Higher Education Institutions, in large part, do not receive financial support for carrying out its activities. Eighteen species of bees raised in these meliponaries were mentioned, the most cited being: Frieseomelitta sp, Melipona subnitida, Melipona scutellaris, Melipona rufiventris, Plebeia sp and Melipona fasciculata. The visiting public is diverse, consisting of students, university students, professionals of​nutrition and gastronomy, among others. Visits take place throughout the year, most of the time, based on prior appointment through the contact available on social networks. The construction of the collaborative map of didactic meliponaries can facilitate and encourage the visitation of people interested in getting to know the bees and, thus, constitute an important instrument, contributing to the development of actions aimed at the conservation of these important insects.